2024
DOI: 10.1021/acs.chemrev.3c00569
|View full text |Cite
|
Sign up to set email alerts
|

A Guide to Printed Stretchable Conductors

Tushar Sakorikar,
Nikolas Mihaliak,
Febby Krisnadi
et al.

Abstract: Printing of stretchable conductors enables the fabrication and rapid prototyping of stretchable electronic devices. For such applications, there are often specific process and material requirements such as print resolution, maximum strain, and electrical/ ionic conductivity. This review highlights common printing methods and compatible inks that produce stretchable conductors. The review compares the capabilities, benefits, and limitations of each approach to help guide the selection of a suitable process and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 256 publications
(545 reference statements)
0
1
0
Order By: Relevance
“…Pre-synthesized CNTs have been patterned by several methods including inkjet printing [ 87 , 88 , 89 ], screen printing [ 90 , 91 , 92 ], gravure printing [ 93 ], and microcontact printing [ 94 , 95 , 96 ]. However, these abovementioned approaches focus on alignment of CNTs for different applications, whereas our research focuses on patterning the catalyst to understand and control the growth mechanism of CNTs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-synthesized CNTs have been patterned by several methods including inkjet printing [ 87 , 88 , 89 ], screen printing [ 90 , 91 , 92 ], gravure printing [ 93 ], and microcontact printing [ 94 , 95 , 96 ]. However, these abovementioned approaches focus on alignment of CNTs for different applications, whereas our research focuses on patterning the catalyst to understand and control the growth mechanism of CNTs.…”
Section: Resultsmentioning
confidence: 99%
“…In our case, we believe that G′ band shift indicates the strain results from mechanical stresses due to high tube length and lack of neighbors support on "empty" spaces of the pattern. Pre-synthesized CNTs have been patterned by several methods including inkjet printing [87][88][89], screen printing [90][91][92], gravure printing [93], and microcontact printing [94][95][96]. However, these abovementioned approaches focus on alignment of CNTs for different applications, whereas our research focuses on patterning the catalyst to understand and control the growth mechanism of CNTs.…”
Section: Cnt Characterizationmentioning
confidence: 99%
“…Several of these challenges can be overcome through emerging techniques in additive manufacturing, which enable digital programmability during printing. Among different material extrusion methods, direct ink writing (DIW) which prints a wide range of inks, from biomaterials to ceramics, is of great interest for printing soft composites. In a typical DIW process, the ink is selectively dispensed through a nozzle on the print bed, controlled by a command script. Recently, it has been shown that by controlling the process conditions, initially spherical LM droplets can be systematically elongated during DIW printing of LM composites.…”
Section: Introductionmentioning
confidence: 99%